Locating home: Newcomer youths’ school and community engagement - Deckers, Chrissy Michelle; Zinga, Dawn (Canadian Journal of Education/Revue canadienne de l'éducation, 2012)
This study explored how diversity among newcomer youth may explain differences in engagement and school success. Youth identifying fear-based reasons for relocation reported being less involved within their schools than those who identified social mobility. In fear-based relocation, youth often viewed Canada as a temporary place to live and gain transportable skills, leading to less school and community engagement. Clearly, as youth approach and connect with school in different ways, understanding the motivations behind youths’ varied levels of engagement could assist school personnel in contextualizing engagement according to youths’ goals. Policy implications are discussed. Keywords: newcomer youth, school and community engagement, motivation for relocation, educational challenges, diversity